SECONDARY AMYLOIDOSIS WITH LUNG INVOLVEMENT INA FEMALE PATIENT WITH RHEUMATOID ARTHRITIS - Irina Mikhailovna Marusenko; Ya A Avdeyeva; I I Polskaya (Современная ревматология)
The paper considers the problem of secondary amyloidosis that more frequently occurs in patients with various arthritides, both seropositive and seronegative. According to the data available in the literature, the most common manifestations of secondary amyloidosis are involvements of the kidney, liver, nervous system, and, less frequently, the lung. The authors describe their own observation of secondary amyloidosis in rheumatoid arthritis, which is accompanied by the involvement of the lung, kidney, and intestine, resulting in fatal outcome. The lifetime diagnosis of amyloidosis was histologically verified.